Generative AI-Assisted Design of Love-Based Curriculum Modules for Islamic Education Teachers - Zakiya Alifatuz; Mubarok Achmat; Wiwin Fachrudin Yusuf; Muhammada Muhammada (Journal of Islamic Education Students (JIES), 2026)
The ability to design effective teaching modules is a fundamental competency for Islamic Education teachers, yet the process is often constrained by curriculum alignment and administrative demands. This study aimed to explore teachers' experiences in designing Love-Based Curriculum teaching modules using Generative Artificial Intelligence (AI). Employing a qualitative approach, data were collected through interviews, observations, and document analysis. The findings reveal that Generative AI supports teachers in organizing instructional components, generating learning ideas, and improving the efficiency of module development while maintaining the values and principles of the Love-Based Curriculum. The effectiveness of AI utilization was determined not by its ability to replace teachers' roles, but by teachers' capacity to critically adapt and integrate AI-generated outputs into meaningful pedagogical practices. The study concludes that Generative AI serves as a valuable support tool for enhancing teachers' capacity in curriculum-based module design while preserving professional judgment and educational values. Further studies are recommended to examine AI-assisted curriculum design across broader educational contexts.